2020
DOI: 10.1002/rcm.8621
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and study of dopant‐assisted photoionization with a miniature capillary inlet ion trap mass spectrometer

Abstract: Rationale Dopant‐assisted photoionization (PI) has been widely used in the mass spectrometric analysis of volatile compounds. Exploring simple doping methods will benefit parameter optimization and promote the application of this technique. Methods A previously built miniature ion trap mass spectrometer was used to study dopant‐assisted vacuum PI. The sampling system of this device was modified to provide three inlets for the simultaneous introduction of analytes, dopants, and auxiliary air. Then, dopant solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Ruskic et al found that the selectivity of DMS for separating isomers depends on the concentration of chiral selectors. Other common chiral selectors are cyclodextrin with metal cations, methanol, anisole, and so on.…”
Section: Applications Of Im-ms For the Separation And Characterizatio...mentioning
confidence: 99%
“…Ruskic et al found that the selectivity of DMS for separating isomers depends on the concentration of chiral selectors. Other common chiral selectors are cyclodextrin with metal cations, methanol, anisole, and so on.…”
Section: Applications Of Im-ms For the Separation And Characterizatio...mentioning
confidence: 99%
“…Ion trap mass spectrometer has been considered an optimum choice because of its moderate vacuum requirements, simple structure, and tandem analysis capability [ 9 ]. The development of ambient ionization methods without sample preparation or separation such as desorption electrospray ionization (DESI) [ 10 , 11 ], direct analysis in real-time (DART) [ 11 , 12 ], photoionization (PI) [ 13 , 14 , 15 ], low temperature plasma (LTP) [ 16 , 17 ], paper spray ionization (PSI) [ 18 , 19 ], further paved the way for MS technology from the laboratory use to onsite applications. The feasibility of combining these ambient ionization methods and miniaturized ion trap mass spectrometer for rapid on-site illegal drugs detection has been demonstrated [ 13 , 14 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the injection method, self-aspiration sampling is a simple and feasible strategy, which has the advantages of easy operation, small dead volume, and less sample consumption. In particular, using the native vacuum chamber of the mass spectrometer to self-pump liquid or gaseous samples can further simplify the assembly. For miniature MS instruments, self-aspiration sampling should be combined with vacuum ionization technology to exhibit practical significance. The common in-vacuum ionization sources, such as electron ionization and photoionization, are typically used for the analysis of gaseous samples.…”
Section: Introductionmentioning
confidence: 99%